<htm>Desenvolvimento gonadal de Deuterodon langei Travassos (Teleostei: Characidae)</htm> - Vitule, J. R. S.; Gazola-Silva, F. F.; Aranha, J. M. R. (Acta Biológica Paranaense, 2007)
Desenvolvimento gonadal de Deuterodon langei Travassos (Teleostei: Characidae)